Oblique water wave diffraction by a step - Dolai, P. (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with the problem of diffraction of an obliquely incident surface water wave train on an obstacle in the form of a finite step. Havelock expansions of water wave potentials are used in the mathematical analysis to obtain the physical parameters reflection and transmission coefficients in terms of integrals. Appropriate multi-term Galerkin approximations involving ultraspherical Gegenbauer polynomials are utilized to obtain a very accurate numerical estimate for reflection and transmission coefficients which are depicted graphically. From these figures various interesting results are discussed.
Keywords: finite step; Havelock expansion; Galerkin approximation; Gegenbauer polynomial; reflection coefficients; transmission coefficients